Catalpol Attenuates Pulmonary Fibrosis by Inhibiting Ang II/AT1 and TGF-β/Smad-Mediated Epithelial Mesenchymal Transition - Yu, Qun; Zhu, Dewei; Zou, Yang; Wang, Kai; Rao, Peili; Shen, Yunhui (Frontiers in Medicine, 2022)
Background Idiopathic pulmonary fibrosis (IPF) is a progressive and devastating chronic lung condition affecting over 3 million people worldwide with a high mortality rate and there are no effective drugs. Angiotensin II (Ang II), as a major effector peptide of the renin angiotensin aldosterone system, has been shown to act in tandem with the transforming growth factor-β (TGF-β) signaling pathway to promote the infiltration of inflammatory cells, production of reactive oxygen species (ROS) and profibrotic factors after lung injury, and to participate in the process of epithelial mesenchymal transition (EMT). Catalpol (CAT) has been shown to have anti-inflammatory and antifibrotic effects. However, the effects and mechanisms of CAT on pulmonary fibrosis are not clear. Purpose To assess the effects and mechanisms of catalpol on bleomycin-induced pulmonary fibrosis in mice. Methods We used bleomycin-induced mouse model of pulmonary fibrosis to evaluate the alleviation effect of CAT at 7, 14, 28d, respectively. Next, enzyme-linked immunosorbent assay, hematoxylin-eosin staining, immunofluorescence, Masson trichrome staining and western blotting were used to study the underlying mechanism of CAT on bleomycin-induced pulmonary fibrosis. Results It's demonstrated that CAT exerted a potent anti-fibrotic function in BLM-induced mice pulmonary fibrosis via alleviating inflammatory, ameliorating collagen deposition, reducing the level of Ang II and HYP and alleviating the degree of EMT. Moreover, CAT attenuate BLM-induced fibrosis by targeting Ang II/AT1 and TGF-β/Smad signaling in vivo. Conclusion CAT may serve as a novel therapeutic candidate for the simultaneous blockade of Ang II and TGF-β pathway to attenuate pulmonary fibrosis.